A trajetória de Asikó: o andarilho: processos pedagógicos da dança-afro na escola - Silva, Carlos Henrique Vidal da (2022)
The present experience report consists of the experience covered for three years as a student at the Atheneu Sergipense State School. The story told here in a playful and narrative way, brings as a possible result a reflection on the applicability of law 10696/003 that governs the mandatory teaching of Afro-Brazilian culture at school. This analysis is based on the experience within the Um Quê de Negritude project, a dance group whose choreographic objective is to explore the movements present in the archetypes of the Orixás and in Afro-Brazilian culture. Using the possibilities to arrive at a pedagogy that can reinforce the teaching of this culture, the Orixá Exu Onan, lord of the paths, is placed as regent to the teaching of these crossroads of knowledge as an educational process, Rufino (2019). In this project, it will also be discussed how ancestry survives from dance, Sabino and Lody (2011), Silva (2021). For the understanding of whiteness, there will be dialogues aimed at the process of hereditary acceptance of Afro-Brazilian culture, resulting in an artistic incentive, as Schucman (2014) and Santos (2021) emphasize. To work on these themes, a performative writing will be used with the creation of a plot and characters for a better linguistic and didactic appreciation in the dance context in which I discuss here.